Effects of dietary genistin supplementation on reproductive performance, immunity and antioxidative capacity in gestating sows - Li, Yuchen; Yu, Bing; Liu, Chunxue; Xia, Shuangshuang; Luo, Yuheng; Zheng, Ping; Cong, Guanglei; Yu, Jie; Luo, Junqiu; Yan, Hui; He, Jun (Frontiers in Veterinary Science, 2024)
Genistin is an isoflavone of soybean, with estrogenic activity. This experiment was conducted to investigate its effect on reproductive performance, antioxidant capacity, and immunity in gestating sows. Seventy-two sows (Landrace × Yorkshire) were selected and randomly divided into two treatment groups (n = 36) based on their backfat thickness, parity and fed with basal diet or supplementation of 150 mg/ kg genistin to the basal diet based on DMI for the entire gestation period. Results showed that dietary genistin supplementation significantly increased the average number of live born per litter (p < 0.05), and tended to increase the number of healthy piglets per litter (p = 0.058), but decreased the average weight of live born per litter (p < 0.05). Dietary genistin supplementation significantly decreased the number of mummified and stillbirths per litter (p < 0.05). Moreover, the average daily feed intake (ADFI) and total feed intake of the gestating sows were also increased in the genistin-supplemented group (p < 0.05). Genistin significantly increased the serum concentrations of catalase (CAT), immunoglobulin A (IgA), IgG, and IgM at 35 days of gestation (p < 0.05). The serum concentrations of interleukin-10 (IL-10) and interferon-γ (IFN-γ) were also increased upon genistin supplementation (p < 0.05). However, genistin supplementation tended to decrease the serum concentrations of total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and leptin at 85 days of gestation (p = 0.081 and p = 0.096, respectively). Interestingly, genistin supplementation decreased the transcript abundance of interferon-γ (IFN-γ) and placental imprinting gene H19, but significantly increased the transcript abundance of insulin-like growth factor I (IGF-I) and amino acid transporters such as the sodium-coupled neutral amino acid transporter 2 (SNTA2) and SNAT4 in the placenta (p < 0.05). These results suggested that dietary genistin supplementation during gestation can improve the reproductive performance of sows, which was probably associated with improving of antioxidant capacity and immunity, as well as changes of transcript abundance of critical functional genes in the placenta.